ANALISIS KERAPATAN JARINGAN STASIUN CURAH HUJAN - Dimu Ratu, Yerison; Krisnayanti, Denik Sri; Udiana, I Made (Jurnal Teknik Sipil, 2012)
The rain that falls on the surface of the earth is influenced by several factors that are not evenly spread to a region of the river. It can be determined by the proper placement of rain station, good location, number and pattern of spread. However, the placement of the rain stations are generally based only on immediate needs, so do not pay attention to the development of water resources as a whole. This research is specifically done on Aesesa with area of 8.202,41 km2. Methods to be used in this study is the method of Kagan. Analysis of the WS Aesesa obtained daily rainfall correlation coefficient 0,184 and 0,293 monthly. Existing density of rainfall stations in the WS Aesesa 1.025,0 km2 /Station. For daily rainfall, averaging 5% error obtained an area 195,295 km2/stations and 42 stations, alignment errors of 10% obtained an area of 585.886 km2/stations and 14 stations. While 5% for monthly rainfall, obtained an area of 182,276 km2/ stations and 45 stations, 10% error obtained an area 546,827 km2/stations and 15 stations. The number of stations is not the only factor affecting the level of rainfall forecast accuracy, but the pattern of spread also plays a role in determining the level of accuracy.